Juridical Analysis of the Withdrawal of Fiduciary Security Objects by Creditors Based on Law Number 42 of 1999 on Fiduciary Security - Dicky Alfrido Ginting; Adi Nur Rohman (Ultimate Journal of Legal Studies, 2026)
Fiduciary security is a form of proprietary security widely used in financing agreements in Indonesia, as it provides creditors with preferential rights and executorial power while allowing debtors to retain possession of the secured object during the term of the agreement. The regulation of fiduciary security is governed by Law Number 42 of 1999, including the mechanism for executing the secured object in the event of default. However, in practice, the execution of fiduciary security frequently gives rise to legal issues, particularly unilateral repossession of secured objects without clear agreement on default or judicial procedures, which may prejudice the rights of debtors. This research aims to analyze the legal regulation governing the mechanism for executing or repossessing fiduciary security objects and to examine the forms of legal protection afforded to creditors and debtors following Constitutional Court Decision Number 18/PUU-XVII/2019. This study employs normative legal research using statutory and conceptual approaches. The findings indicate that the Constitutional Court Decision emphasizes that the executorial power of fiduciary certificates cannot be exercised unilaterally without an agreement regarding default and voluntary surrender by the debtor or a court decision with permanent legal force. This decision strengthens the principle of due process of law and promotes a more balanced legal protection framework for both creditors and debtors in the execution of fiduciary security.